The Influence of Students’ Attitudes towards Authentic Assessment on Mathematics Learning Outcomes - Santoso, Agus; Widyastuti, Suciati Rahayu (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2025)
This study aims to analyze the influence of students’ attitudes in the application of authentic assessment on mathematics learning outcomes of junior high school students in Cirebon City. This study uses a quantitative approach with a correlational method. The research sample consisted of 361 grade VII students in several junior high schools in Cirebon City. The data analysis technique used was simple linear regression to test the influence between independent and dependent variables. The results showed that students’ attitudes towards authentic assessment have a positive and significant effect on mathematics learning outcomes. Students’ attitudes in this case are influenced by perceptions of teachers, parents, and peers. The implications of this study emphasize the importance of forming positive attitudes through active teacher involvement and parental support in the learning process based on authentic assessment.